(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the article, guides play an important role in promoting the richness of historical and cultural heritage, in awakening tourists’ great interest in our material and cultural heritage, and in increasing the promotion of tourism services.